Receptor for advanced glycation end products mediates inflammation and enhanced expression of tissue factor in vasculature of diabetic apolipoprotein E null mice - Kislinger, Thomas; Tanji, Nozomu; Wendt, Thoralf; Qu, Wu; Lu, Yan; Ferran, Luis J.; Taguchi, Akihiko; Olson, Kim; Bucciarelli, Loredana; Goova, Mouza; Hofmann, Marion A.; Cataldegirmen, Guellue; et al. (Arteriosclerosis, Thrombosis, and Vascular Biology, 2001)
Advanced glycation end products (AGEs) and their cell surface receptor, RAGE, have been implicated in the pathogenesis of diabetic complications. Here, we studied the role of RAGE and expression of its proinflammatory ligands, EN-RAGEs (S100/calgranulins), in inflammatory events mediating cellular activation in diabetic tissue. Apolipoprotein E-null mice were rendered diabetic with streptozotocin at 6 weeks of age. Compared with nondiabetic aortas and kidneys, diabetic aortas and kidneys displayed increased expression of RAGE, EN-RAGEs, and 2 key markers of vascular inflammation, vascular cell adhesion molecule (VCAM)-1 and tissue factor. Administration of soluble RAGE, the extracellular domain of the receptor, or vehicle to diabetic mice for 6 weeks suppressed levels of VCAM-1 and tissue factor in the aorta, in parallel with decreased expression of RAGE and EN-RAGEs. Diabetic kidney demonstrated increased numbers of EN-RAGE-expressing inflammatory cells infiltrating the glomerulus and enhanced mRNA for transforming growth factor-β, fibronectin, and α1 (IV) collagen. In mice treated with soluble RAGE, the numbers of infiltrating inflammatory cells and mRNA levels for these glomerular cytokines and components of extracellular matrix were decreased. These data suggest that activation of RAGE primes cells targeted for perturbation in diabetic tissues by the induction of proinflammatory mediators.
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.llmch.recept
Keywords: Atherosclerosis; Diabetes; Glycation; Nephropathy; Receptor for advanced glycation end products